Chapter «Perscrutando o passado encontro o mito do tempo». L'Oriente di António Correia - Correia, António (Studi di Traduzione Letteraria Lusofona, 2023)
This article aims to present the Lusitanian soul of António Correia, focusing on his deep relationship with Asia, specifically with India and Macao and the remembrance of the golden age of the Portuguese presence in Asia.